Sosialisasi Legalitas Usaha Bagi Pelaku UMKM di Kabupaten Jember - Siti Mukaromah; Iva Dwi Mahyudah; Sherly Maulidia Sari (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Business legality is a sign or indication that a business entity has been legally recognized by the State. So business legality is very important for business actors. However, based on data collection on MSMEs in Jember Regency, of the 155 MSMEs in the data, only 50 MSMEs have business legality. From interviews with business actors, information was obtained that the reason they did not have business legality was because they lacked knowledge about the procedures for obtaining business legality and the process which was considered quite difficult. Therefore, this socialization conveyed the importance of having business legality for MSME players.